2013
DOI: 10.1021/es402300m
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Duck Eggs: An Important Pathway of Human Exposure to PBDEs around E-Waste and Scrap Metal Processing Areas in Eastern China

Abstract: Although consumption of local foods is recognized as an important pathway of human exposure to PBDEs in areas of China involved in rudimentary recycling of electronic waste (e-waste), dietary intake studies to date have not considered the contribution from consumption of duck eggs, despite being a common dietary component. Fresh duck eggs (n = 11) were collected from each of five farms located within 500 m of e-waste recycling workshops in the Wenling and Luqiao districts of Taizhou City, Eastern China, in Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 39 publications
3
21
3
Order By: Relevance
“…By contrast, if considering approximately 10% lipid content in eggs, Labunska et al (2015) reported higher levels of EH-TBB (average: 4.3 ng/ g lw) and similar levels of BEH-TEBP (average: 1.1 ng/g lw) in poultry eggs from another e-waste recycling area in southern China. Similar to our findings, the concentrations of EH-TBB and BEH-TEBP in their egg samples were only 2e5 times higher than the levels (or LOQ) for control site, while distinctive differences of persistent contaminants, such as PBDEs, hexabromocyclododecane (HBCD) and polychlorinated biphenyls (PCBs) could be seen in eggs from e-waste sites and control sites (1e3 orders of magnitude higher in eggs from e-waste sites than control sites) (Labunska et al, 2013(Labunska et al, , 2015Zheng et al, 2012).…”
Section: Levels Of Target Frs In Home-produced Eggssupporting
confidence: 87%
“…By contrast, if considering approximately 10% lipid content in eggs, Labunska et al (2015) reported higher levels of EH-TBB (average: 4.3 ng/ g lw) and similar levels of BEH-TEBP (average: 1.1 ng/g lw) in poultry eggs from another e-waste recycling area in southern China. Similar to our findings, the concentrations of EH-TBB and BEH-TEBP in their egg samples were only 2e5 times higher than the levels (or LOQ) for control site, while distinctive differences of persistent contaminants, such as PBDEs, hexabromocyclododecane (HBCD) and polychlorinated biphenyls (PCBs) could be seen in eggs from e-waste sites and control sites (1e3 orders of magnitude higher in eggs from e-waste sites than control sites) (Labunska et al, 2013(Labunska et al, , 2015Zheng et al, 2012).…”
Section: Levels Of Target Frs In Home-produced Eggssupporting
confidence: 87%
“…Generally, the ranges of OHP concentrations reported here for chicken eggs were one to two orders of magnitude higher than those observed in chicken eggs from the other sites (Covaci et al, 2009;Hu et al, 2011;Labunska et al, 2014Labunska et al, , 2015; however, they were comparable to those observed in chicken eggs collected from Qingyuan (an e-waste recycling region in South China) (Zheng et al, 2012) (Table S1). The OHP (except for SCCPs, TBBPA and HBB) levels in chicken eggs from site 2 were significantly lower than those from site 1 (One-way ANOVA: p < 0.05), an observation which was a priori expected, due to the greater distance between the farm and the e-waste recycling center (Fig.…”
Section: Inter-site and Inter-species Differences In Ohp Levelscontrasting
confidence: 59%
“…In May 2009, the Stockholm Convention classified penta-and octa-BDE commercial formulations as persistent organic pollutants because of their toxic effects. Both production and use of penta-and octa-BDEs have been banned for several years in the European Union and elsewhere (Labunska et al 2013). Decabromodiphenyl ether (BDE-209) also exhibits toxic properties in animals and can be metabolized in the environment to form toxic lessbrominated PBDEs (La Guardia et al 2007;Kajiwara et al 2008;Labunska et al 2013).…”
Section: Responsible Editor: Ester Heathmentioning
confidence: 99%
“…Both production and use of penta-and octa-BDEs have been banned for several years in the European Union and elsewhere (Labunska et al 2013). Decabromodiphenyl ether (BDE-209) also exhibits toxic properties in animals and can be metabolized in the environment to form toxic lessbrominated PBDEs (La Guardia et al 2007;Kajiwara et al 2008;Labunska et al 2013). Although its use was phased out in North America and Europe, deca-BDE is still being produced and used in many countries, including China (Ni et al 2013).…”
Section: Responsible Editor: Ester Heathmentioning
confidence: 99%